Combining laboratory X-ray powder diffraction and microtomography for studying cement hydration - García-Aranda, Miguel Ángel (My University, 2023)
Se da en documento adjunto con gráficos.
Keywords: Química inorgánica; Mineralogía; Cristalografía; Tomografía; Multimodal; Diffraction; Tomography; Microstructure